LEGAL IMPACT OF DEBT DEFAULT IN FATWA DSN-MUI NO. 11/2000 (CASE STUDY OF MICRO WAQF BANK MAWARIDUSSALAM) - Fitri Hidayanti Hasibuan; Dhiauddin Tanjung; Mhd. Yadi Harahap (SOSIOEDUKASI, 2025)
The purpose of this study is to determine the legal impact of debt default in the DSN-MUI fatwa. 11/2000. This research will discuss the legal regulation of debt coverage agreements according to the provisions of DSN-MUI Fatwa No. 11 of 2000. Then the legal answer due to the default in the debt coverage agreement and the legal impact of debt coverage on the provision of capital through the Mawaridussalam Micro Waqf Bank. This research uses a normative legal approach. The data used as the basis for this research is secondary data, which consists of various sources such as books, scientific journals, and academic articles. The results of the research show that the legal regulation of debt coverage agreements according to the provisions of DSN-MUI Fatwa No. 11 of 2000 is that later the bank will get service rewards or fees for kafalah financing carried out based on sharia principles and if the guarantor does not carry out its obligations that have been due, it must pay compensation. Legal liability due to default in the debt coverage agreement is The position of the individual insurer as the guarantor of the debtor's debt has an obligation to fulfill the payment of debts owned by the debtor when the debtor is unable to pay off his debt. If the insurer consists of more than one person, then the liability of the debtors, each of which is bound for all debts or known as the term bearing. The consequences of the Debt Coverage Law on the provision of capital through the Mawaridussalam Micro Waqf Bank are the role of the Mawaridussalam Islamic boarding school in the economic empowerment of the community through the business unit of the Islamic boarding school of the Sharia Micro Waqf Bank, namely: Getting loan assistance in the form of money for capital to continue the business and business development; Releasing the public from loan sharks and financial institutions with an interest or riba system; Experiencing an increase in daily income and an increase in religious knowledge. From the results of interviews with resource persons who are customers of the Sharia Micro Waqf Bank at the Mawaridussalam Islamic Boarding School.